Hiperconto no Ensino de Língua Portuguesa: pop ups como forma de mediação da leitura literária - PEREIRA, Paula Cristina Damante (2018)
This research proposes the mediation of literary reading, in Portuguese Language classes of Elementary School, planned and developed from Digital Information and Communication Technologies, present in digital media. We argue that the digital resources typical of these supports can make a great contribution to the process of teaching and learning, especially with regard to reading strategies that contemplate literary productions published in cyberspace. The theories to support the presented ideas combines the dialogue between researchers in the area of Literature and Digital Technologies of Information and Communication. Thus, the study was based on Rildo Cosson for the proper treatment of Literary Literacy; in Regina Zilberman and Antônio Cândido, respectively, for the reflection on the educational character and the importance of considering the literary practice as a right and Vera Maria Tietzmann Silva for the defense of the mediation of reading of literary texts. For the discussions about current virtual reading spaces, as well as digital literary productions and their specificities, this work associates scholars like Denise Bértoli Braga, Pierre Lévy, Carla Viana Coscarelli and Katherine Hayles. In this way, we seek to investigate the possibility of leading students to show greater interest in the reading of literary texts produced from digital resources typical of hypertext. Through the action research, we try to prove the hypothesis that the students subject of this research can broaden their literary reading experiences through mediator texts present in pop ups - windows that open from a connection point. The study was carried out with 26 students from the 9th year of Elementary School in a public school in the countryside area of São Paulo state, which revealed that they had the daily habit of hypertextual reading present in social networks and transmitted through the internet. To prove the relevance of teacher mediation and shared reading in the classroom, we have read two short stories, "The Barrel of Amontillado" and "The Fall of the House of Usher," both by Edgar Allan Poe. The students filled a form about the experience of this activity in the classroom, endorsing our defense on the need to follow and verify the understanding and interpretation of the reader in training. The observations were concluded with the application of the intervention proposal that consisted of reading without the presence mediation of the hyperconto "The Black Cat" - an extension of the printed story, by Edgar Allan Poe, marked by hypertextual structure and organization - produced for digital support and published on the internet in the domain https://contosdigitais.000webhostapp.com/OGatoPreto21.html. The results show that the motivational texts present in the pop ups collaborate for a productive reading, even though it is performed without the presence of the researcher teacher and reading mediation agent, sincethey act as auxiliary content whose objective is to perform interventions previously considered relevant to that moment and age, and that are materialized by the mediating teacher in moments of shared reading.